Early onset metastatic colorectal cancer in Australia - A. Jalali; S. Smith; G. Kim; H. Wong; M. Lee; J. Yeung; M. Loft; R. Wong; J.D. Shapiro; S. Kosmider; J. Tie; S. Ananda; et al. (Cancer Treatment and Research Communications, 2024)
Background: Colorectal cancer (CRC) incidence and mortality rates have been increasing among young patients (YP), for uncertain reasons. It is unclear whether YP have a distinct tumor biology or merit a different treatment approach to older patients (OP). Methods: We reviewed prospectively collected data from consecutive patients with metastatic CRC (MCRC) enrolled in the multi-site Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) Australian registry. Clinicopathological features, treatment and survival outcomes were compared between YP (<50 years) and OP (≥50 years). Results: Of 3692 patients diagnosed August 2009 - March 2023, 14 % (513) were YP. YP were more likely than OP to be female (52% vs. 40 %, P < 0.0001), have ECOG performance status 0–1 (94% vs. 81 %, P < 0.0001), to have a left-sided primary (72% vs. 63 %, P = 0.0008) and to have fewer comorbidities (90% vs. 60 % Charleston score 0, P < 0.0001). There were no differences in the available molecular status, which was more complete in YP. YP were more likely to have de novo metastatic disease (71% vs. 57 %, P < 0.0001). YP were more likely to undergo curative hepatic resection (27% vs. 17 %, P < 0.0001), to receive any chemotherapy (93% vs. 78 % (P < 0.0001), and to receive 3+ lines of chemotherapy (30% vs. 24 % (P < 0.0034)). Median first-line progression free survival (10.2 versus 10.6 months) was similar for YP vs OP, but overall survival (32.1 versus 25.4 months, HR = 0.745, P < 0.0001) was longer in YP. Conclusion: Known prognostic variables mostly favored YP versus OP with newly diagnosed mCRC, who were also more heavily treated. Consistent with this, overall survival outcomes were improved. This data does not support that CRC in YP represent a distinct subset of mCRC patients, or that a modified treatment approach is warranted.